Research on Insurance Company Underwriting Decisions based on Breakeven Analysis Multi-Objective Planning Model - Wu, Ji (Transactions on Economics, Business and Management Research, 2024)
Extreme weather events are increasingly becoming a crisis for insurance companies, posing significant challenges to their financial stability. These events lead to higher claim frequencies and magnitudes, demanding more robust risk assessment and management strategies. This paper constructs a multi-objective programming model based on breakeven analysis, determines the regional risk level through risk assessment, and calculates the breakeven point. When the number of insurance policies exceeds the breakeven point, the insurance company will underwrite the region. The underwriting plan is the Pareto optimal solution, and the insurance company can choose the plan with a large number of insured but low profit, or choose the plan with a high insurance profit but low quantity. This model aims to provide underwriting decision-making guidance for insurance companies, ensuring their long-term healthy operation.